The vehicle routing problem: State of the art classification and review. (September 2016) - Braekers, Kris; Ramaekers, Katrien; Van Nieuwenhuyse, Inneke
Highlights: Taxonomic review of vehicle routing literature published between 2009 and mid 2015. An adapted version of an existing comprehensive taxonomy is presented. 277 VRP articles are classified based on problem characteristics and assumptions. The classification table allows researchers to quickly find relevant literature. Recent trends in VRP literature are discussed. Abstract: Over the past decades, the Vehicle Routing Problem (VRP) and its variants have grown ever more popular in the academic literature. Yet, the problem characteristics and assumptions vary widely and few literature reviews have made an effort to classify the existing articles accordingly. In this article, we present a taxonomic review of the VRP literature published between 2009 and June 2015. Based on an adapted version of an existing comprehensive taxonomy, we classify 277 articles and analyze the trends in the VRP literature. This classification is the first to categorize the articles to this level of detail.